APOε4 is associated with enhanced in vivo innate immune responses in human subjects - Gale, Stephen C.; Gao, Li; Mikacenic, Carmen; Coyle, Susette M.; Rafaels, Nicholas; Murray Dudenkov, Tanda; Madenspacher, Jennifer H.; Draper, David W.; Ge, William; Aloor, Jim J.; Azzam, Kathleen M.; Lai, Lihua; et al. (Journal of allergy and clinical immunology, 2014)
The genetic determinants of the human innate immune response are poorly understood. Apolipoprotein (Apo) E, a lipid-trafficking protein that affects inflammation, has well-described wild-type (ε3) and disease-associated (ε2 and ε4) alleles, but its connection to human innate immunity is undefined. We sought to define the relationship of APOε4 to the human innate immune response. We evaluated APOε4 in several functional models of the human innate immune response, including intravenous LPS challenge in human subjects, and assessed APOε4 association to organ injury in patients with severe sepsis, a disease driven by dysregulated innate immunity. Whole blood from healthy APOε3/APOε4 volunteers induced higher cytokine levels on ex vivo stimulation with Toll-like receptor (TLR) 2, TLR4, or TLR5 ligands than blood from APOε3/APOε3 patients, whereas TLR7/8 responses were similar. This was associated with increased lipid rafts in APOε3/APOε4 monocytes. By contrast, APOε3/APOε3 and APOε3/APOε4 serum neutralized LPS equivalently and supported similar LPS responses in Apoe-deficient macrophages, arguing against a differential role for secretory APOE4 protein. After intravenous LPS, APOε3/APOε4 patients had higher hyperthermia and plasma TNF-α levels and earlier plasma IL-6 than APOε3/APOε3 patients. APOE4-targeted replacement mice displayed enhanced hypothermia, plasma cytokines, and hepatic injury and altered splenic lymphocyte apoptosis after systemic LPS compared with APOE3 counterparts. In a cohort of 828 patients with severe sepsis, APOε4 was associated with increased coagulation system failure among European American patients. APOε4 is a determinant of the human innate immune response to multiple TLR ligands and associates with altered patterns of organ injury in human sepsis.